The sustainable MBA : a business guide to sustainability - Weybrecht, Giselle (Chichester, West Sussex : Wiley, 2014)
IThe Sustainable MBA/i provides the knowledge and tools to help you "green" your job and organization, to turn sustainability btalk/b into baction/b for the benefit of your bottom line and society as a whole. Based on more than 100 interviews with experts in business, international organizations, NGOs and universities from around the world, this first of its kind guide brings together all the pieces of the business and sustainability puzzle including:ulliThe basics on what sustainability is, why you should be interested, how to get started, and what a sustainable organization looks like.liA wide range of tools, guidelines, techniques and concepts that you can use to implement sustainability practices.liTools and tips on how to "green" your job, including how to sell these ideas to your team, how to make green choices as a consumer and how to organize green meetings.liA survey of the exciting trends in sustainable business happening around the world.liA wealth of links to interesting resources for more information./ul iThe Sustainable MBA/i is organized like a business school course ' allowing you easy access to the relevant information you need about sustainability and bAccounting, Economics, Entrepreneurship, Ethics, Finance, Marketing, Organizational Behaviour, Operations and Strategy./b bGiselle Weybrecht's/b commitment to sustainable development goes back to before her university years. Since then she has expanded her reach to local and national government, business, social entrepreneurs, and the international community. She worked for the United Nations World Water Assessment Programme, is a fellow of the UC Berkeley-based Beahrs Environmental Leadership Programme, and holds an MBA from London Business School. She is currently developing new approaches to raise awareness among managers of how they can incorporate sustainability into their businesses and everyday professional lives.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Management -- Environmental aspects; Business enterprises -- Environmental aspects; Sustainable development; Social responsibility of business; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior; Business enterprises -- Environmental aspects; Management -- Environmental aspects; Social responsibility of business; Sustainable development; Electronic books